The Effect of Emotion Regulation on Marital Flourishing in Married Couples in Sumbawa - Imammul Insan; Kholifah Rosdiyati (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine whether there is an effect of Emotion Regulation on Marital Flourishing in married couples in Sumbawa Regency. This study uses a descriptive quantitative approach. Sampling using the Slovin Technique. Data analysis technique using simple regression. The sample of this research was n = 40 samples of n = wife and husband so that the total became n = 80. The results showed that the effect of emotion regulation on marital flourishing was with a sig value of 0.000 <0.05 and an R Square of 0.775. Which means the higher the emotional regulation, the better the marital flourishing. Emotion regulation has an effect of 77.5% while the remaining 33.5% is influenced by other variables not examined